Technologies and Chemistry teachers: a brazilian professional development program (Revista Internacional de Formação de Professores, 2022)
The education sector is one of the social spheres directly affected by digital technologies. Attentionto the paths taken by such apparatuses is vital to understanding one's own educational processes.In this situation, the training of teachers is included. Thus, the aim is to present the general nuancesof the Professional Development Program for Teachers with the purpose of contextualizing aninnovative strategy of teacher training of the public basic education network based on the trainingactions developed in the area of Chemistry. The program was offered by the Brazilian governmentto the teachers of basic education through an international cooperation agreement between Braziland Portugal. The training took place at the University of Porto and the University of Aveiro. Theywere offered 175 vacancies for teachers from all regions of Brazil. in the areas of PortugueseLanguage, Pedagogy, Physics, Mathematics and Chemistry. The Chemistry area was the only onethat occurred in both partner institutions, being monitored in loco. So it is important to divulge thecontexts of its occurrence and the same time the value of the teachers of the national public network.